Variations on a theme: crystal forms of the amino‐acid transporter MhsT. Issue 8 (26th July 2022) - Neumann, Caroline; Focht, Dorota; Trampari, Sofia; Lyons, Joseph A.; Nissen, Poul
Abstract : An unusual case of protein–substrate complexes that were obtained under similar conditions but contain different packing arrangements is reported. The crystals exhibit a combination of various crystal imperfections (pseudosymmetry, twinning and translational noncrystallographic symmetry), masking the true crystal symmetry and challenging data processing and structure determination. Abstract : The bacterial amino‐acid transporter MhsT from the SLC6A family has been crystallized in complex with different substrates in order to understand the determinants of the substrate specificity of the transporter. Surprisingly, crystals of the different MhsT–substrate complexes showed interrelated but different crystal‐packing arrangements. Space‐group assignment and structure determination of these different crystal forms present challenging combinations of pseudosymmetry, twinning and translational noncrystallographic symmetry.